Genetic and functional homologous repair deficiency as biomarkers for platinum sensitivity in TNBC: A case report - Gomez-Puerto, Diego; Llop-Guevara, Alba; Cruellas, Mara; Torres-Esquius, Sara; De La Torre, Javier; Peg, Vicente; Balmaña, Judith; Pimentel, Isabel (Frontiers in Oncology, 2022)
Triple-negative breast cancer is the most aggressive subtype of mammary carcinoma. In the early-stage neoadjuvant chemotherapy is the standard of care for prognostic stratification and best adjuvant treatment strategy. A 30-year-old female consulted to the emergency room because of a gigantic right breast associated to an ulcerated lump at the upper quadrants. Right axillary nodes were palpable. An ultrasound was performed showing the ulcerated neoformation with enlarged right axillary lymph nodes observed till level III. A core biopsy of the breast lesion was performed, and the pathological examination revealed a non-special type, grade 3 invasive triple negative breast cancer. No distant disease was found in the PET-CT scan. Germline genetic panel by next generation sequencing identified a likely pathogenic variant in RAD51D (c.898C>T). Assessment of the functionality of the DNA homologous recombination repair pathway by RAD51 foci in the tumor revealed a profile of homologous recombination deficiency. Neoadjuvant chemotherapy consisting of weekly carboplatin and paclitaxel followed by dose dense doxorubicin/cyclophosphamide was performed with a complete metabolic response achieved in the PET-CT scan. The patient underwent a modified radical mastectomy plus axillary lymphadenectomy, with a pathological complete response in the breast and axilla and remains disease free after 1and a half year of follow-up. We report a young female with a triple negative breast cancer stage cT4bN3M0 and a hereditary pathogenic mutation in RAD51D. The tumor was highly proliferative and homologous recombination deficient by RAD51. The patient received platinum-based neoadjuvant chemotherapy achieving a pathologic complete response. More effort should be made to identify predictive functional biomarkers of treatment response, as RAD51 foci, for platinum sensitivity.